2014
DOI: 10.1002/marc.201300916
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biocompatible Glycodendrimer based on Fluorescent Perylene Bisimides and Its Bioimaging

Abstract: A novel water-soluble fluorescent glycodendrimer based on perylene bisimides is synthesized, which exhibits high fluorescence quantum yield of 54%. While the binding interactions of PBI-Man with Concanavalin A (Con A) are studied by fluorescence spectra and CD spectra, which show strong binding affinity for Con A with the binding constant of 3.8 × 10(7) m(-1) for monomeric mannose, nearly four orders of magnitude higher affinity than the monovalent mannose ligand. Furthermore, the fluorescence imaging of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…1,33,35 On the other hand dendritic glycoconjugates, carbohydrate-containing dendronized polymers, and hybrid materials of various polysaccharides over the last year have been also established in various application fields. Thus they have been used as drug delivery systems, 10, biosensors, 15,16,19,[96][97][98][99][100][101] and imaging agents, 1,18,[102][103][104][105][106] but also as a base in biohybrid structures obtained through non-covalent and biological conjugation, 91,92,107,108 as sugarballs for H-bond-active therapeutics and diagnostics for brain disease, [109][110][111][112][113][114][115][116][117][118] as supramolecular structures by (defined) self-assembly [119][120][121] or host-guest interactions, 122 and in thin film technology for introducing specific interactions with small analyte molecules or proteins. 123,124 The PPI, Lys, and PAMAM polyamine dendrimers, but also branched poly(ethyleneimines) (PEI) are the dominating dendritic core scaffolds to realize the desired dendritic glycopolymers for these growing research fields ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,33,35 On the other hand dendritic glycoconjugates, carbohydrate-containing dendronized polymers, and hybrid materials of various polysaccharides over the last year have been also established in various application fields. Thus they have been used as drug delivery systems, 10, biosensors, 15,16,19,[96][97][98][99][100][101] and imaging agents, 1,18,[102][103][104][105][106] but also as a base in biohybrid structures obtained through non-covalent and biological conjugation, 91,92,107,108 as sugarballs for H-bond-active therapeutics and diagnostics for brain disease, [109][110][111][112][113][114][115][116][117][118] as supramolecular structures by (defined) self-assembly [119][120][121] or host-guest interactions, 122 and in thin film technology for introducing specific interactions with small analyte molecules or proteins. 123,124 The PPI, Lys, and PAMAM polyamine dendrimers, but also branched poly(ethyleneimines) (PEI) are the dominating dendritic core scaffolds to realize the desired dendritic glycopolymers for these growing research fields ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction with macrophage-like cell lines (highly mannosylated on their surface) of the PDI-based glycocluster was then investigated leading to another "turn-on" fluorescence, and the MMP inhibition talked above could be directly studied by cell-imaging. Another similar study from this group 63 reported another 18-valent mannosylated PDI-based glycocluster for bioimaging of murine macrophage cells. Clearly, these two latter studies have extended the applications of PDI-based glyco-probes to biomedical areas.…”
Section: Perylenediimide-based Glycoconjugatesmentioning
confidence: 86%
“…Poor water solubility and high lipophilicity of these dyes hamper their use in bioimaging because they precipitate out in biological media. In the past few years, various functional groups, such as protonated amines, polyglycerol dendrones, and carboxylic or sulfonic acid on the imide position or in the bay area, have been employed to increase the water solubility of PBIs for biological applications …”
Section: Methodsmentioning
confidence: 99%